Hybrid compression-encryption-watermarking image algorithm based on the quaternionic wavelets transform (QWT) - Ndongo Hervé, Abena; Ebassa Bertrand Ledoux, Eloundou; Malobe Paul, Abena; Alexendre, Noura (International Journal of Engineering and Technology, 2021)
In this article, we present a robust new hybrid algorithm combining successive compression, chaotic encryption, and blind watermarking images based on the quaternionic wavelets transform (QWT) to ensure the fast, simple and secure transfer of digital data. The calculations of the various evaluation parameters were carried out with the aim of determining the robustness of our algorithm against certain attacks. The results obtained of the reconstructed images before and after attacks of the compressed-encrypted-watermarked images are appreciated by calculating the evaluation parameters values and by the human visual system. The application of this hybrid algorithm on CFA images al-lowed us to obtain a stand-alone transmission system and ensure the integrity of digital data.